2020
DOI: 10.1016/j.neuropharm.2020.108118
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for multiscale computational modelling of serotonergic drug effects in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is an age-specific neurodegenerative disease that compromises cognitive functioning and impacts the quality of life of an individual. Pathologically, AD is characterised by abnormal accumulation of beta-amyloid (Aβ) and hyperphosphorylated tau protein. Despite research advances over the last few decades, there is currently still no cure for AD. Although, medications are available to control some behavioural symptoms and slow the disease's progression, most prescribed medications are ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…AKT phosphorylates and consequently inactivates glycogen synthase kinase-3 (GSK3) that phosphorylates tau protein. 5HTR 2 could modulate GSK3 phosphorylation through protein kinase C (PKC) [ 50 ] and β-arrestin-mediated signaling [ 51 ], while 5HTR 4 , 5HTR 6 , and 5HTR 7 could modulate GSK3 phosphorylation through protein kinase A (PKA) [ 50 ]. Several studies also observed an association between APOE and 5HT receptors.…”
Section: Discussionmentioning
confidence: 99%
“…AKT phosphorylates and consequently inactivates glycogen synthase kinase-3 (GSK3) that phosphorylates tau protein. 5HTR 2 could modulate GSK3 phosphorylation through protein kinase C (PKC) [ 50 ] and β-arrestin-mediated signaling [ 51 ], while 5HTR 4 , 5HTR 6 , and 5HTR 7 could modulate GSK3 phosphorylation through protein kinase A (PKA) [ 50 ]. Several studies also observed an association between APOE and 5HT receptors.…”
Section: Discussionmentioning
confidence: 99%
“…While depression had an OR value of 1.32 (FDR p<0.001) suggesting that it is associated with increased risk of progression, however, treatment of the disorder with certain antidepressants can protect against this risk. Studies have suggested that SARIs like trazodone exhibit neuroprotective properties when examined in mammalian cell cultures and in neurodegenerative mouse models (Halliday et al, 2017) with complex cellular signalling pathway mechanisms (Joshi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Multiscale and multilevel modelling approaches attempted to provide new insights into AD mechanisms and can be further expanded to identify novel therapeutic targets and pharmacological treatments such as the serotoninergic system, which has been deeply investigated through computational methods over the last decade [ 133 ].…”
Section: Modeling Diseasesmentioning
confidence: 99%